Liver abscesses ultrasonic semiotics and its significance for the surgery method choosing - Yareshko, V. G.; Zhivitsa, S. G.; Otarashvili, K. N.; Novak, V. V.; Krivoruchko, I. V. (Modern medical technology, 2019)
Significant progress has now been made in diagnosing, treating, reducing complications and lethality at liver abscesses. This is due to the displacement from the arsenal of surgery of complex and traumatic abdominal or trans thoraces approach to abscesses, which themselves created the problem of the postoperative period, complicated the course of an already severe infectious pathology. Modern minimally invasive technologies have significant advantages, especially with regard to interventional sonography, that is, the combined properties of diagnosis and treatment. Purpose of the study. To objectify the choice of the method of surgical intervention of liver abscesses on the basis of a new self-developed ultrasound semiotics of the stage of the formation of abscesses. Materials and methods. A comprehensive examination of 62 patients with liver abscesses was based on the study of the clinical picture of the liver abscesses, a bacteriological study of the contents, CT scan, and especially ultrasound, on the basis of which the ultrasound semiotics of the stages of the formation of abscesses was developed and implemented. Results and discussion. According to the possibilities of ultrasound diagnosis of abscesses of the liver from the first signs of local inflammation in the liver to the final stage of formation of the pyogenic capsule, we identified four stages of their development: 1 stage – local inflammatory changes of the parenchyma without its destruction; Stage 2 – destructive changes of parenchyma without signs of distinct boundaries; Stage 3 – clear boundaries of destructive changes with a non-expressed capsule; Stage 4 – clear formation of a capsule with complete destruction of tissues. The proposed ultrasonic semiotics allows us to determine the method of operation. Thus, at stages 1 and 2, and in some cases in 3 stages, there is no alternative to puncture-drainage methods in residual postoperative cavities. At stages 3 and 4, there are more advantages in laparoscopic operations, in some cases laparotomic. Conclusions. the proposed classification of ultrasonic semiotics stages of the formation of liver abscesses most pathogenetically corresponds to the morphological changes of the abscess zone and, most importantly, is adapted to the choice of the method of operation.